PENGARUH PENGGUNAAN MULTI MEDIA TERHADAP KEMAMPUAN BERBICARA BERBAHASA INGGRIS PADA SISWA SMA HANGTUAH 4 SURABAYA TAHUN PELAJARAN 2016 - 2017 - Sulistiyani (Fakultas Ekonomi Universitas 45 Surabaya, 2016)
The use of youtube, facebook, blogging, whatsapp, and twitter for purposes of learning by creating groups on the interests of certain discussion to do in the community. As a result of the rapid social media development has downloaded the social behavioural pattern. Gradually lead to the integrations that brings learning activities to be done in multimedia and used technology in education, because media in education has important role in communication. English is one of foreign language subject which has taught at schools.English lessons apply in all forms of social relations, both at school and in association community with the structure and function of each use education as media that will be tought and be the effectiveness lesson. So the objectives specified in the use of multimedia learning can be achieved in stimulating learning, students dare to ask questions, answer questions or comment on the content being delivered also increased teacher.